Corps feminin, corps saccage, corps mutile: la vie sans fard de la femme opprimee dans Je suis nee au harem de Choga Regina Egbeme (2016)
The theory of objectification of female body highlights the question of the subjugation of woman. This phenomenon causes a virulent violence done to women by men, reducing the former to her body without regard for her personality and integrity. For decades, feminists oppose this challenge of making the woman an object of sexual desire and re / production . Choga Regina Egbeme’s Je uis nee au harem ( I was born in harem) highlights the appalling damage that men do to women and raises the principle of the oppression of women in a notoriously hegemonic society. The experience of papa David’s wives and daughters throughout the autobiographic narrative is the testimony of many African women. Following her forced marriage to a downright aggressive man, who raped her, and consequently infected with HIV by him and the baby resulted from the rape, Choga, the eponymous protagonist of the novel, secretly fled the prison home where she lives with her co-wives to help children and women who fall victims of this scourge. This article is based on a purely autobiographical novel which bitterly denounces the subjugation of the African woman caught in an ethos gearing, of diseases and even thorny traditions. Despite years of anti-hegemonic feminist campaigns that emphasises revalorisation of the female body, it is found that the female body remains a political site of patriarchal force.